Implementasi Penggunaan Jaringan Intranet Menggunakan Linux Ubuntu Server Implementasi Penggunaan Jaringan Intranet Menggunakan Linux Ubuntu Server - Andree Adhi Dharma; Khairil Khairil; Feri Hari Utami (Jurnal Media Infotama, 2024)
The computer network at Sumur Meleleh Subdistrict is designed to support administrative activities, but its installation lacks consideration for equipment availability. The chosen research method is the Network Development Life Cycle, involving stages such as analyzing device requirements, designing network and system infrastructure, simulating to minimize errors, implementing system creation, monitoring devices on installed systems, and managing maintenance for technology adjustments. The successful implementation of an intranet network, utilizing an Ubuntu server as the system, has effectively optimized the sub-district office network. This intranet network assigns IP addresses to computers and serves as a provider for client devices, thereby enhancing employee performance efficiency according to research findings.